Use of depressants in the direct flotation of a silicate-carbonate phosphate ore - Adalberto Leles de Souza (Rem: Revista Escola de Minas, 2014)
A high demand for mineral resources observed in recent decades has led to an expansion in production in the mining industry. Different process alternatives have been proposed for selective separation between apatite and contaminants (carbonates and silicates) present in phosphate ores. Magnetic separation, calcination and gravity separation processes are methods that present low efficiency and high cost. Flotation is the most common process; however the selectivity is hampered by the superficial similarity of the chemical composition of phosphates and carbonates, high surface activity of the collectors used, interactions between dissolved ionic species of certain mineral with another and also interactions between dissolved ionic species and re - agents. In this study, conducted in a laboratory scale, eight different depressants, or - ganic and inorganic, were tested in the direct flotation of a Brazilian silicate-carbonate phosphate ore. The best performance in the depression of calcite and silicates was achieved with cassava starch.